2016
DOI: 10.1002/ptr.5701
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous and Ethanolic Extracts of Boswellia serrata Protect Against Focal Cerebral Ischemia and Reperfusion Injury in Rats

Abstract: Oxidative stress and cell apoptosis play major roles in neuronal injury after ischemia-reperfusion (I-R) injury. Boswellia serrata is a medicinal plant with antioxidant properties. Acetyl-11-keto-β-boswellic acid (AKBA) is an active triterpenoid compound from B. serrate. In the current study, the neuroprotective effects of aqueous and ethanolic extracts of B. serrata (named ABS and EBS, respectively) and AKBA were investigated against middle cerebral artery occlusion-induced cerebral I-R injury in rats. ABS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…In terms of herbal medicines, increasing demand for medicinal plants and related compounds has been spurred by their global use for the treatment of a myriad of diseases. 16 bright orange yellow in color. It is also known as diferuloylmethane.…”
Section: Herbal Medicine Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of herbal medicines, increasing demand for medicinal plants and related compounds has been spurred by their global use for the treatment of a myriad of diseases. 16 bright orange yellow in color. It is also known as diferuloylmethane.…”
Section: Herbal Medicine Strategymentioning
confidence: 99%
“…In recent times, the belief that natural medicines having fewer side effects than synthetic drugs have become very popular and has led to a huge increase in phytopharmaceutical usage throughout the world. In terms of herbal medicines, increasing demand for medicinal plants and related compounds has been spurred by their global use for the treatment of a myriad of diseases …”
Section: Herbal Medicine Strategymentioning
confidence: 99%
“…The levels of MDA, as the final product of lipid peroxidation process, were determined using thiobarbituric acid (TBA), as the reagent. 23,24 Briefly, 100 μL of serum was mixed with 2 mL of TCA-TBA-HCl reagent (15% trichloroacetic acid, 0.67% TBA, and 0.25 N HCl) and heated for 45 minutes in a boiling…”
Section: Measurement Of Mdamentioning
confidence: 99%
“…The amount of MDA produced was calculated in μmol/L. 23 Determination of sOD activity SOD activity in serum was evaluated using a spectrophotometric method. 25 Briefly, the sample was incubated in a solution containing Tris-HCl buffer (pH 8.2, 50 mM) and EDTA (1 mM).…”
mentioning
confidence: 99%
“…In another study, it has been showed that treatment with hydroalcoholic extract of saffron improves spatial learning and memory in rats with cerebral ischemia through carotid artery ligation Boswellia serrata can be consider as a useful plant to treat cerebral ischemia due to oral administration of aqueous and ethanolic extracts obtained from Boswellia serrata lead to reduction of neurological deficit and brain infarction [23]. In addition, this extract has antioxidant and anti-apoptotic effect through reduction of lipid peroxidation and increase of glutathione level and superoxide dismutase activity as well as reduction of caspase-3 activity, down regulation of bax and up regulation of bcl-2 in rats with middle cerebral artery occlusion-induced cerebral ischemia-reperfusion injury [24]. In a study effect of ethanolic extract prepared from Embelia.…”
Section: Plant Extract and Their Role In Cerebral Ischemia Treatmentmentioning
confidence: 99%